Numerical Analysis Method of Shear Properties of Infilled Joints under Constant Normal Stiffness Condition - Xiangyu Wang; Ruofan Wang; Zizheng Zhang (Advances in Civil Engineering)
The direct shear test is implemented in this paper for infilled joints under constant normal stiffness (CNS) condition with the finite difference software FLAC3D. The CNS condition was performed based on a servoprogram developed by FISH language. The effects of initial normal stress, undulating angle, and infilled ratio on the shear failure mode of infilled joints under CNS are revealed based on numerical simulation. It is found that the shear strength of infilled joints will grow along with the increase of the undulating angle and the decrease of the infilled ratio. The numerical analysis method is also able to quantify the effect of multiple factors (initial normal stress and infilled ratio) on shear properties of infilled joints. The model shows a good agreement with the experimental results available in the literatures. Therefore, this study proposed and verified a numerical analysis method capable of studying the effects of normal stress, undulating angles, and infilled ratio on the shear behavior of infilled rock joints.